Efeito da lectina jacalina (artocarpus integrifolia) sobre a sobrevivência e ativação in vitro de folículos primordiais caprinos - Ribeiro, Regislane Pinto (2013)
The aims of this study were to investigate the effect of different concentrations of jacalin and the interaction of jacalin and FSH on survival, activation and gene expression of goat primordial follicles cultured in vitro. For this, fragments of ovarian cortex were cultured in Minimum Essential Medium (MEM) supplemented with different concentrations of jacalin (0, 10, 25, 50 and 100 mg/mL - experiment I) for one and six days. After the end of cultured period, the fragments of ovarian cortex were fixed for histology. Then, the percentage of primordial follicles in uncultured or cultured ovarian tissue in different treatments were evaluated. After determining the most effective concentration of jacalin (50 μg/mL), ovarian cortex fragments were cultured in MEM supplemented with jacalin (50 μg/ml), FSH (50 ng/ml) or both (experiment II). After 6 days of culture, the ovarian fragments were fixed for histology. Furthermore, for each treatment, tissue samples were collected to evaluate the expression profile of mRNA for c-kit, KL, GDF-9, BMP-15 and PCNA in goats ovarian follicles cultured in vitro for 6 days. The results showed that after six days of culture, the presence of 50 μg/ml jacalin in culture medium increased the percentage of normal follicles, and promoted a reduction in the percentage of primordial follicles and increase of developing follicles, when compared to control medium. In experiment II, jacalin or FSH stimulated primordial follicle activation and contributed to maintain follicle viability, but there was no positive interaction between these two substances. The levels of mRNA for BMP-15 and KL after in vitro culture of ovarian fragments in different treatments was not altered. However, the presence of FSH increased levels of mRNA for c-kit and PCNA, while the GDF-9 expression was reduced in medium supplemented with jacalin. In conclusion, jacalin and FSH were able to promote the survival and activation of goat primordial follicles after 6 days of culture. The presence of FSH increased expression mRNA of PCNA and c-kit, while the presence of jacalin reduced the expression of GDF-9.